COMPARATIVE ANALYSIS OF CUTTING FORCES AND TEMPERATURES IN MICRO-MILLING OF AUSTENITIC AND MARTENSITIC NITI ALLOYS BASED ON FINITE ELEMENT MODELLING - BALYTSKA, NATALIIA; TOMASHEVSKYI, OLEH (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Today, micromilling is actively used in many industries due to the rapidly growing demand for miniature, high-precision products. Compared to conventional milling, micromilling is characterised by much more difficult chip formation conditions and dramatically higher specific cutting forces. The low machinability of NiTi alloys results in high specific cutting energy, cutting forces and temperatures, high tool wear and excessive burr formation during micromilling. The crystallographic structure and the physical and mechanical properties of the NiTi alloy depend on its phase state and influence the characteristics of the cutting process. This article compares the physical, mechanical and functional properties of austenitic and martensitic NiTi alloys. The aim of the work is to compare cutting forces and temperatures and to investigate the dependence of the specific cutting force on the scale coefficient during micromilling of austenitic and martensitic NiTi alloys using finite element modelling. For the investigation, finite element modelling of the process of micromilling grooves on NiTi alloy workpieces with a 0.5 mm diameter milling cutter under variable cutting conditions was applied in the DEFORM-3D software environment. The adequacy of the developed finite element model was confirmed by comparing the results of modelling and experimental measurements of cutting forces. The dependence of the components of the cutting forces and cutting temperatures on the feed rate and the dependence of the specific cutting forces on the scale factor were obtained. A comparative analysis of the data made it possible to identify trends in the variation of cutting forces and temperatures under variable machining conditions for NiTi alloy in the austenitic and martensitic phase state, which is of practical importance for the justified selection of cutting conditions. The results obtained will help to increase the efficiency of manufacturing products with micro-elements and improve the technology of micro-milling of NiTi alloys.